Establishment of transfusion‐relevant bacteria reference strains for red blood cells. Issue 6 (20th December 2020) - Prax, Marcel; Spindler‐Raffel, Eva; McDonald, Carl Peter; Bearne, Jennifer; Satake, Masahiro; Kozakai, Moe; Rojo, Julieta; Hanschmann, Kay‐Martin O.; Lambrecht, Bernd; Grundmann, Udo; O'Flaherty, Niamh; Klimek, Agata; et al.
Abstract: Background and objectives: Red blood cell concentrates (RBCC) are susceptible to bacterial contamination despite cold storage. A reliable evaluation of strategies to minimize the risk of RBCC‐associated bacterial transmission requires the use of suitable reference bacteria. Already existing Transfusion‐Relevant Bacteria Reference Strains (TRBRS) for platelet concentrates fail to grow in RBCC. Consequently, the ISBT TTID, Working Party, Bacterial Subgroup, conducted an international study on TRBRS for RBCC. Materials and methods: Six bacterial strains ( Listeria monocytogenes PEI‐A‐199, Serratia liquefaciens PEI‐A‐184, Serratia marcescens PEI‐B‐P‐56, Pseudomonas fluorescens PEI‐B‐P‐77, Yersinia enterocolitica PEI‐A‐105, Yersinia enterocolitica PEI‐A‐176) were distributed to 15 laboratories worldwide for enumeration, identification, and determination of growth kinetics in RBCC at days 7, 14, 21, 28, 35 and 42 of storage after low‐count spiking (10–25 CFU/RBCC). Results: Bacterial proliferation in RBCC was obtained for most strains, except for S. marcescens, which grew only at 4 of 15 laboratories. S. liquefaciens, S. marcescens, P. fluorescens and the two Y. enterocolitica strains reached the stationary phase between days 14 and 21 of RBCC storage with a bacterial concentration of approximately 10 9 CFU/ml. L. monocytogenes displayed slower growth kinetics reaching 10 6 –10 7 CFU/ml after 42 days. Conclusion: The results illustrate the importance of conducting comprehensive studies to establish well‐characterized reference strains, which can be a tool to assess strategies and methods used to ameliorate blood safety. The WHO Expert Committee on Biological Standardization adopted the five successful strains as official RBCC reference strains. Our study also highlights the relevance of visual inspection to interdict contaminated RBC units.